Confucianism and democratization in East Asia - Shin, Doh Chull (Cambridge University Press, 2011)
"This book examines how Confucianism affects the development of democratic citizenship in East Asia. To what extent do East Asians remain attached to the particular way of life and system of government that Confucius and Mencius advocated to bring about a community of grand harmony? How does such attachment to Confucian civic norms affect their engagement in civic affairs? How does attachment to Confucian paternalistic meritocracy affect their commitment to democracy? The book addresses these question in the context of public opinion surveys conducted in East Asia and other regions" -- Provided by publisher